NEW INEQUALITIES FOR LOCAL FRACTIONAL INTEGRALS PERTAINING GENERALIZED STRONGLY CONVEX MAPPINGS - Kashuri, Artion; Zeki Sarikaya, Mehmet (Matematichki Bilten, 2020)
In this paper, we first obtain a generalized integral identity for twice local fractional differentiable mappings on fractal sets \(R^α\) (\(0<α≤ 1\)) of real line numbers. Then, using twice local fractional differentiable mappings that are in absolute value at certain powers generalized strongly convex, we obtain some new estimates on generalization of trapezium-like inequalities. We also discuss some new special cases which can be deduced from our main results.